Comparison of CIMT with PNF versus NMES with PNF to improve Upper Limb Function in Hemiparetic Patients (International Journal of Physiotherapy, 2026)
Background: Stroke frequently results in motor and sensory deficits leading to functional dependence. After a stroke, upper-limb weakness is prevalent throughout the different phases of recovery, impacting daily activities and QoL. Current rehabilitation approaches have incorporated evidence-based techniques to enhance upper limb recovery. Proprioceptive neuromuscular facilitation (PNF) employs particular movement patterns to aid the improvement of muscle function and strength in stroke patients. Constraint-induced movement therapy (CIMT) is an extensively researched strategy for treating upper-limb deficits following stroke, demonstrating improvements in motor function with forced-shift paradigms. Additionally, Neuromuscular electrical stimulation (NMES) has been shown to improve motor control by facilitating recovery of volitional movement. Although the individual therapies have proven effective, the comparativeeffect of the combination therapies has yet to be explored. Hence, our study aims to compare the effectiveness of CIMT with PNF versus NMES with PNF in enhancing upper-limb function in hemiparetic patients.Methods: The comparative study was done with 30 stroke patients. The patients aged 50-70 in the sub-acute stage of stroke with MAS